Radiographic detection of defects in friction stir welding on aluminum alloy AMg5M; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Tarasov S. Yu. Sergei Yulievich (2014, 2014)
Title screen